Mengeksplorasi Manfaat Aplikasi Tanggung Jawab Sosial (SR App) dalam Mengoptimalkan Tata Kelola Program Pengembangan Masyarakat: Studi pada Yayasan Inovasi Muda Indonesia - Lisdawati Wahjudin; Ridho Rinaldi (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
The growing integration of digital technologies into organizational operations has transformed the governance landscape, particularly for non-profit institutions managing complex community development programs. This study examines the role of a Social Responsibility Application (SR App) in enhancing the governance performance of community empowerment initiatives through a digital platform. Using a descriptive qualitative approach, the research focuses on the Inovasi Muda Indonesia Foundation. This non-profit organization has adopted the SR App to improve its social programs' efficiency, transparency, and accountability. Data were collected through in-depth interviews, observations, and secondary sources, involving five purposively selected users of the SR App. The findings reveal several benefits of the application, including a more structured governance workflow, real-time program monitoring, accelerated and interactive reporting, and improved data analytics for strategic decision-making. These insights demonstrate how digital transformation can support non-profit organizations in implementing good governance practices and achieving greater impact through technology-enabled community development. The study offers practical implications for other non-profits aiming to strengthen their governance through e-governance tools.